Analysis of the consumption volumes of antithrombotic drugs used for pharmacotherapy of atrial fibrillation in Saratov Region - А. V. Sokolov; О. V. Reshet'ko (IRBIS LLC, 2022)
Objective: To study the evolution of consumption of antithrombotic drugs used for the treatment of atrial fibrillation (AF) at the outpatient stage in the Saratov Region using the ATC/DDD (Anatomical Therapeutic Chemical Classification / Defined Daily Doses) and drug utilization 90% (DU90%) analysis.Material and methods. We analyzed the outpatient stage of treatment using the data reflected in 511 case histories of AF patients hospitalized in specialized cardiology departments of the Saratov Region in 2011-2018. The study of the consumption volumes of antithrombotic drugs was carried out using the ATC/DDD- and DU90%-analysis methodology. The consumption of drugs with proven efficacy in AF was expressed as the number of daily doses (NDDD) per 1000 AF patients per day.Results. In 2011, the number of prescribed DDD of oral anticoagulants (OACs) was 5.29 NDDD per 1000 AF patients per day, and all of them were represented by warfarin; in 2018, this indicator increased up to 277.51 NDDD per 1000 AF patients per day, of which direct OACs amounted to 237.06. The consumption of antiplatelet agents remained at a high level, and in 2018, was 582.53 NDDD per 1000 AF patients per day. Acetylsalicylic acid was included in the group of drugs accounting for 90% of all antithrombotic drugs at the outpatient stage - 99.02% in 2011, 93.08% in 2012, 58.55% in 2016, 60.27% in 2017, and 46.66% in 2018.Conclusion. The consumption volumes of OACs used at the outpatient stage of treatment of AF in the Saratov Region increased significantly in the period from 2011 to 2018, mainly due to direct OACs. At the same time, the consumption volumes of antiplatelet agents remained at a high level.